The Influence of the Work Environment and Work Morale on Employee Performance With Work Quality as a Variable Intervening at Bank Syariah Indonesia Area Medan Raya - Syahnant; Mesra B (Yayasan Multidimensi Kreatif, 2024)
A conducive work environment and high morale are very important factors in achieving optimal performance quality in the face of increasingly fierce industry competition. The purpose of this study is to find out and analyze the influence of the work environment and work morale on employee performance mediated by the quality of work at Bank Syariah Indonesia in the Medan Raya area. This research was conducted with a causal associative quantitative approach. The sample used was 100 employees taken from 287 populations with a random sample technique using the slovin formula. The results of data analysis used Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results of the study showed that the work environment had no effect on employee performance, with a T-statistical value of 0.043 < 1.96 and a P-value of 0.966 > 0.05, so that the improvement of the work environment would not improve employee performance. On the contrary, work morale has a positive and significant influence on employee performance, shown by a T-statistical value of 4.963 > 1.96 and a P-value of 0.000 < 0.05, indicating that increasing work morale can improve employee performance. The work environment also had a positive and significant effect on the quality of employees' work, with a T-statistical value of 3.048 > 1.96 and a P-value of 0.003 < 0.05. However, work morale did not have a significant effect on the quality of employee work, with a T-statistical value of 1.335 < 1.96 and a P-value of 0.185 > 0.05. In addition, the quality of work did not have a significant effect on employee performance, with a T-statistical value of 1.181 < 1.96 and a P-value of 0.240 > 0.05. The quality of work is also unable to intervene in the influence of the work environment on employee performance, shown by the T-statistical value of 1.151 < 1.96 and the P-value of 0.253 > 0.05. Similarly, work quality was unable to intervene in the influence of work morale on employee performance, with a T-statistical value of 0.645 < 1.96 and a P-value of 0.521 > 0.05. These results provide insight that factors such as work environment and work morale do not have a mediating effect through work quality on employee performance at Bank Syariah Indonesia in the Medan Raya area.